Pengembangan Sumber Daya Manusia Melalui Peningkatan Kompetensi Pegawai Negeri Sipil Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Kepulauan Siau Tagulandang Biaro Provinsi Sulawesi Utara - Jenerson Patonengan; Irfan Setiawan (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2021)
This research is based on the importance of developing human resources through increasing competence in order to realize competent Civil Servants in the administration of government in the field of personnel administration. This is intended to study and analyze the development of human resources through increasing competence in the Agency for Personnel and Human Resources Development, Siau Islands Regency, Tagulandang Biaro, North Sulawesi Province. This research is descriptive, using an inductive qualitative approach, with data collection techniques through interviews, observation, and documentation. In this study, it was revealed that the Implementation of Human Resource Development Through Competency Improvement was classified as not effective, caused by factors namely Knowledge, Skills and Attitudes/Behavior of Civil Servants. The need for commitment and a strong desire for the Personnel and Human Resources Development Agency of Siau Islands Regency Tagulandang Biaro, North Sulawesi Province to pay attention to human resource development through increasing the competence of Civil Servants, to meet the quality standards of civil servants who have professional knowledge, skills and attitudes/behaviors.